Effects of Ramadan Fasting on Recovery Following a Simulated Soccer Match in Professional Soccer Players: A Pilot Study - Bouzid, Mohamed Amine; Abaïdia, Abd-Elbasset; Bouchiba, Mustapha; Ghattassi, Kais; Daab, Wael; Engel, Florian A.; Chtourou, Hamdi (Frontiers in Physiology, 2019)
Objectives: Assessing the effects of Ramadan fasting on recovery following a soccer match simulation. Methods: Eight elite soccer players (age: 21.0 ± 0.4 years) performed a modified Loughborough Intermittent Shuttle Test protocol (LISTmod) on two occasions: one week before (BR) and during the fourth week of Ramadan (End-R). At BR and End-R, soccer players performed squat jump, countermovement jump, maximal voluntary contraction, 20 meter sprint and creatine kinase, uric acid and subjective ratings (feelings scale, quality of sleep, fatigue, muscle soreness and stress) were assessed at baseline and 0, 24, 48 and 72 hours following LISTmod. Results: Following LISTmod, performance in squat jump (48h and 72h) (p<0.05), countermovement jump (48h and 72h), maximal voluntary contraction (0h, 24h, 48h and 72h) and 20 meter sprint (0h and 48h) decreased significantly on both occasions. Decreases were higher at End-R than BR. Creatine kinase levels increased significantly at 24h and 48h at BR and End-R (p<0.05).Uric acid increased at 0h and 24 h only on BR. Muscle soreness increased throughout the recovery period at both occasions, with a higher level at End-R. Stress rating increased only at 0h on End-R, while fatigue rating increased at 24h at BR and at 0h, 24h and 48h at End-R. Conclusion: Perturbations in physical performance and subjective ratings parameters were higher at the end of Ramadan. However, the results of this study showed that Ramadan fasting did not adversely affect the recovery following soccer match simulation in professional soccer players.